Potency Labeling of Novel Factor VIII and Factor IX Concentrates: Past Experience and Current Strategy - Hubbard, Anthony R. (Seminars in Thrombosis and Hemostasis, 2015)
Various strategies to produce “longer-lasting” factor VIII and factor IX concentrates through chemical and genetic modifications are currently under evaluation. It is now clear that these new molecules are amenable to testing using conventional methods for biological activity (one-stage clotting and chromogenic) and there is a preference to maintain labeling in International Units (IU) traceable to the WHO International Standard Concentrates. This is an achievable goal; however, many of the new molecules are associated with potency discrepancies both between methods and also within methods, for instance, when different activated partial thromboplastin time reagents are used. In the interests of global harmonization, it is important for licensing authorities to reach agreement on the choice of the potency labeling method. This choice should be supported by a thorough characterization of product potency, both in vitro and in vivo, to anticipate future issues and with a view to maintaining equivalence of the IU compared with existing licensed products. In cases where the product potency is defined using specific reagents, the robustness of the manufacturer's product standard will be crucial for product consistency. The sensitivity of measured potency to different methodologies will require manufacturers to provide guidance to clinical laboratories on suitable postinfusion testing approaches.
Keywords: hemophilia; factor VIII; factor IX; coagulation